Organisational factors influencing non-pharmacological management of type 2 diabetes mellitus (T2DM) in public hospitals across Lagos, Nigeria: A qualitative study of nurses' perspectives. (August 2020) - Bosun-Arije, Foluke Stella; Ling, Jonathan; Graham, Yitka; Hayes, Catherine
Highlights: Information and knowledge management is a factor influencing T2DM management. Policy and decision management is a factor influencing T2DM management. Relationship management is a factor influencing T2DM management. The above factors can hinder patients from making positive health decisions. Flexible and collaborative approaches are low-cost strategies to manage T2DM. Abstract: Background: The prevalence and incidence of Type 2 Diabetes mellitus (T2DM) are significantly increasing in Nigeria. Effective management of the condition, in clinical settings, can be achieved with a minimal financial cost, but this is often overlooked. It is crucial to understand organisational factors influencing non-pharmacological management of T2DM in Nigerian public hospitals for effective management of patients diagnosed with the condition. Aim: To examine healthcare delivery services influencing patient management and seek approaches to heighten optimisation of patient health outcomes. Methods: Adopting a qualitative case study design, we used the Constant Comparative Method and semi-structured questions to interview17 nurses in public hospitals across Lagos. Using the five stages of the Framework Analysis process, the transcribed interviews were thematically analysed. Results: Nurses suggested that a complex, multifaceted system constituted organisational factors influencing T2DM management in public hospitals across Lagos, Nigeria. Specific factors identified were levels of available information and knowledge, relationship, policy and decision-making management. These factors were, in turn, linked to political, infrastructural, health professional and the environments within which patients were given health services. Conclusions: The study revealed a significant gap in the organisation of care for individuals diagnosed with T2DM in public hospitals across Lagos. Timely and affordable strategies have been highlighted to secure effective care delivery to patients.